Impact of TRPV3 on the development of allergic dermatitis as a dendritic cell modulator. Issue 12 (December 2013) - Yamamoto‐Kasai, Erika; Yasui, Kiyoshi; Shichijo, Michitaka; Sakata, Tsuneaki; Yoshioka, Takeshi
Abstract The transient receptor potential channel vanilloid subfamily V member 3 (TRPV3), which functions as a thermosensor in keratinocytes, plays an important role in the development of allergic and itchy dermatitis in rodents. Although real‐time PCR analysis using lesional and non‐lesional skin samples from patients with atopic dermatitis showed that TRPV3 was expressed in lesional skin, the role that TRPV3 plays in patients with dermatitis is still relatively obscure. Here, we determined whether TRPV3 was a dendritic cell (DC) modulator using DS‐Nh mice with a gain‐of‐function mutation in TRPV3 (TRPV3Gly573Ser), because increasing skin temperature is associated with the modulation of dermal dendritic cells (DCs). Interestingly, increased responses to haptens by skin and DCs were observed in DS‐Nh mice compared with those from DS mice with wild‐type TRPV3. Increased thymic stromal lymphopoietin (TSLP) responses were also observed in keratinocytes from DS‐Nh mice compared with those from DS mice. Taken together, we propose that the DS‐Nh mouse is a good model to use in order to better understand the role of this orphan channel and that TRPV3 may represent a new therapeutic target in certain types of dermatitis through the control of DCs.